1989
DOI: 10.1007/bf03005377
|View full text |Cite
|
Sign up to set email alerts
|

pH-Adjustment of 2-chloroprocaine quickens the onset of epidural anaesthesia

Abstract: pH-Adjustment of 2-chloroprocaine quickens the onset of epidural anaesthesia The effect of pH.adjustment of three per cent 2-chloroprocaine (2-CP , Nesacaine MPF | on the onset, duration, and spread of epidural analgesia and anaesthesia was studied in patients undergoing lower extremity surgery. Forty ASA physical status l and II patients were randomized to two groups. In a doubleblinded fashion, patients in both groups received an epidural injection of 15 ml of local anaesthetic (I.A) solution via a Tuohy nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…Clinical studies have demonstrated a more prolonged onset of epidural analgesia and anesthesia when the pH of local anesthetics has been adjusted away from the physiologic range. 18,19 Elucidation of the mechanism of epidural washout will have to await further study.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have demonstrated a more prolonged onset of epidural analgesia and anesthesia when the pH of local anesthetics has been adjusted away from the physiologic range. 18,19 Elucidation of the mechanism of epidural washout will have to await further study.…”
Section: Discussionmentioning
confidence: 99%
“…Significant reductions in onset time have been claimed for extradural mepivacaine [28], lignocaine [22], bupivacaine [24] and chloroprocaine [64,75]. All investigators do not agree with these findings, however, especially with respect to bupivacaine [76].…”
Section: Alkalinization (Ph Adjustment)mentioning
confidence: 98%
“…10,12 The salt, being a weak base, can exist in solution as an un-ionized free base, which is more lipophilic, or as a positively charged cation; both species are involved in the process of conduction blocking. 10,13 The base crosses the neuronal bilayer more easily, and thus is preferred for optimal penetration. 10 The percentage of drug in the two forms depends on its pK a and the environmental pH.…”
mentioning
confidence: 99%
“…Each drug has a characteristic pK a , with ester type LAs typically having a higher value than the amide type. 11 The closer the pK a is to the pH of the tissues, the faster is the onset of action of the drug, 13,14 since the percentage of free base formed increases. For this reason, in infected tissues, the LA effect is reduced or even delayed, as the environment tends to be more acidic than usual and the un-ionized form decreases.…”
mentioning
confidence: 99%